How Women Are Portrayed in Opinion in the Kompas Daily Newspaper According to Sara Mills' Critical Discourse Studies? - Bahardur, Iswadi; Afrinda, Putri Dian; Delpa, Delpa (ppjbsip, 2024)
This research is motivated by the problem of gender inequality issues in women's lives that are still often reported by the mass media. Among the mass media that reported this was the daily newspaper Kompas, especially in an opinion piece entitled Perempuan dan Mimpinya published on June 6, 2024. Based on the background of the problem depicted in the Women and Their Dreams (Perempuan dan Mimpinya) opinion, the purpose of writing this article is to describe how women are viewed by the mass media and their relationship to the current social reality of society. The collection of research data was carried out using reading techniques, including the steps of reading carefully and repeatedly the opinions that were the source of research data, marking vocabulary, phrases, sentences, and paragraphs that were in accordance with the criteria of the research problem, recording and inventorying them in an inventory table. The data was analyzed using an interactive method to reveal the position of women behind the text Women and Their Dreams (Perempuan dan Mimpinya) and its relationship to the current social reality of society. Analysis of the research data shows three things. First, the position of the subject in the discourse of the Perempuan dan Mimpinya opinion is occupied by the author who acts as the storyteller, while the position of the object is occupied by women. Second, the author tries to direct the reader to become the actor of the story by presenting a pseudo reality and cultural code in the text that seems to be the reality in the reader's real life. Third, the meaning of the entire discourse of opinion on Women and Their Dreams shows that in the domestic and public spaces women are still not fully able to become a gender group that is equal to the masculine gender group.